(3GNJUGQ SjQI QShd Gddg Udi Gddg Ydjg hSdes - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3Yi Hf CMeO Hf CMeO s)
(3ChdgG (B:s
(3CeG HYO aEfi GNJUQJ ai gPG GdLRA eG jSgd Ydi GdeQjO MaXg ef PcQ fSH QShd Gddg Udi Gddg Ydjg hSde, hUaJg ai Ndbg hNdbg hSjQJg s
(3BNQgG (B:s
(3agPG ef CjGJg Udi Gddg Ydjg hSde, hCjGJg CcKQ ef Gf JMUi QhjfGgG hQBjfGgG ai fahSfG Je GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B40s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B12 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs